Padlet in teaching and learning / Sri Yusmawati Mohd Yunus … [et al.]. - Mohd Yunus, Sri Yusmawati; Yusof, Rozianiwati; Abdul Rahman, Normaziah; Hashim, Norhafizah; Aziz Fadzillah, Nor Azlina (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
Padlet is an online virtual bulletin board or collaboration platform that allows users to create and share digital boards for various purposes. It is a versatile tool used in education, business and other contexts for wide range of activities including collaboration, sharing information and presentations. As a Padlet user, we can apply Padlet in a variety of contexts and for different purposes and it is highly customizable. Here are some common areas where Padlet can be applied: In education, educators can use it as a classroom collaboration, organize lesson plans, materials, and resources on Padlet boards, post assignments and collect student responses and students can create digital portfolios showcasing their work and achievements. In business, teams can use Padlet for brainstorming, project planning and sharing updates, create digital meeting agendas, share the documents and resources with meeting attendees and collect the customer feedback and ideas on Padlet boards.